PSIX-38 Influence of quebracho (Schinopsis balansae) tannin extract fed at differing rates in a high-roughage diet on energy partitioning in beef steers. (5th December 2019) - Norris, Aaron B; Crossland, Whitney L; Tedeschi, Luis O; Foster, Jamie L; Muir, James P; Pinchak, William
Abstract: Our objective was to evaluate how quebracho tannin (QT; Schinopsis balansae) within a roughage-based diet affected energy partitioning of growing beef steers. Ruminant production is essential to meeting the protein requirements of an increasing global population. However, gaseous byproducts from ruminant production, such as methane (CH4 ), not only reduce energetic efficiency, it can also be detrimental to the environment. Feed-grade antibiotics have traditionally been utilized for improved feed efficiency; however, consumer perception has prompted the pursuit of natural rumen modulators. Condensed tannins are a potential alternative due to their capacity for enhancing protein efficiency and reducing CH4 . In our study, a 4 x 8 Latin rectangle design utilizing four periods and 8 British crossbred steers (236 ± 16 kg) were used to determine the effects of QT fed at 0 (control), 1.5, 3, and 4.5% of DM, within a roughage-based ration. Following 12-d dietary adaptation, animals were relocated to open-circuit respiration calorimetry chambers fitted with metabolism stands for gas exchange measurements and collection of total feces and urine over 48 h. Data were analyzed using a random coefficients model with animal and period as random factors. Inclusion of QT had no effect on intake, fiber digestibility, or nitrogen retention (P > 0.10). Provision of QT increased fecal energy, resulting in reduced digestible energy (DE) (P < 0.01). Urinary energy was not different (P = 0.49) but gas energy decreased (P < 0.01) as QT inclusion increased. Metabolizable energy (ME) decreased linearly as QT increased (P < 0.01), but all treatments maintained a ME-to-DE ratio of 0.86. Heat energy decreased (P = 0.01) with increased QT rate; however, there was no difference in retained energy. Although QT reduced gas and heat energy, this could not compensate for the reduction in digestible energy, leading to decreased energetic efficiency with QT inclusion.